Whale optimization with random contraction and Rosenbrock method for COVID-19 disease prediction. (May 2023) - Zhang, Meilin; Wu, Qianxi; Chen, Huiling; Heidari, Ali Asghar; Cai, Zhennao; Li, Jiaren; Md. Abdelrahim, Elsaid; Mansour, Romany F.
Highlights: An intelligent prediction model to discriminate the severity of COVID-19 is proposed, which combines an improved whale optimization algorithm (RRWOA) with k-nearest neighbor classifier. Random contraction strategy and modified Rosenbrock method are introduced, which enhance the exploration and exploitation respectively. RRWOA shows its competitiveness on IEEE CEC2014, and the model performs best on 15 UCI datasets and the COVID-19 dataset. Abstract: Coronavirus Disease 2019 (COVID-19), instigated by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has hugely impacted global public health. To identify and intervene in critically ill patients early, this paper proposes an efficient, intelligent prediction model based on the machine learning approach, which combines the improved whale optimization algorithm (RRWOA) with the k-nearest neighbor (KNN) classifier. In order to improve the problem that WOA is prone to fall into local optimum, an improved version named RRWOA is proposed based on the random contraction strategy (RCS) and the Rosenbrock method. To verify the capability of the proposed algorithm, RRWOA is tested against nine classical metaheuristics, nine advanced metaheuristics, and seven well-known WOA variants based on 30 IEEE CEC2014 competition functions, respectively. The experimental results in mean, standard deviation, the Friedman test, and the Wilcoxon signed-rank test are considered, proving that RRWOA won first place on 18, 24, and 25 test functions, respectively. In addition, a binary version of the algorithm, called BRRWOA, is developed for feature selection problems. An efficient prediction model based on BRRWOA and KNN classifier is proposed and compared with seven existing binary metaheuristics based on 15 datasets of UCI repositories. The experimental results show that the proposed algorithm obtains the smallest fitness value in eleven datasets and can solve combinatorial optimization problems, indicating that it still performs well in discrete cases. More importantly, the model was compared with five other algorithms on the COVID-19 dataset. The experiment outcomes demonstrate that the model offers a scientific framework to support clinical diagnostic decision-making. Therefore, RRWOA is an effectively improved optimizer with efficient value.